Effectors and Effector Delivery in Magnaporthe oryzae - Zhang, Shijie; Xu, Jin-Rong (PLoS pathogens, 2014)
[...]Slp1 functions to suppress chitin-induced plant immune responses, including generation of reactive oxygen species and expression of defense-related genes [12]. Furthermore, no specific protein motifs or sequences have been identified in the cytoplasmic or apoplastic effectors that are responsible for their localization in plant cells after being secreted. [...]it is impossible to predict whether an effector is apoplastic or cytoplasmic solely based on its amino acid sequence. [...]unlike the 39.3 kD Pwl2-mCherry fusion, the 68.3 kD Pwl2-tdTomato protein was defective in the movement from the penetrated cells to surrounding cells [17]. [...]cell-to-cell effector translocation also depends on the protein size.